Advanced basal cell carcinomas of the face: A Moroccan series - Sara Elloudi; Aida Oulehri; Hanane Baybay; Zakia Douhi; Fatima Zahra Mernissi (Our Dermatology Online, 2021)
Background: Basal cell carcinoma (BCC) is the most common cutaneous skin malignancy. 85% of BCCs affect the face, a region particularly rich in noble organs. Although BCC progresses slowly, considerable local destruction and mutilation may be observed. Material and Methods: We performed a retrospective review of the database stored by our institution. All patients with histologically confirmed mutilating basal cell carcinoma of the face hospitalized at the dermatology department of the university hospital in Fez, Morocco, from 2015 through 2020 were evaluated. Results: Nine patients were included, with the tumors located in the lips, temporal region, orbital region, and cheeks, with sizes varying from 5 to 11 cm. Conclusion: In the series, we were able to highlight the high-risk character of the subpopulation living in rural areas and the role of smoking as a major risk factor.